MONITORING KUALITAS AIR TAMBAK DENGAN WQ (WATER QUALITY) INTERPRETER - Pahlewi, Anita Diah; Damayanti,; Handayani, Creani; Widiarti, Dian (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
The Association of Panarukan Situbondo’s Shrimp Farmers at Panarukan Sub-district, Situbondo Regency, raises white vaname shrimp in a polyculture method in their ponds in a simple way, relying on instinct with their limited knowledge about the importance of IPAL and water quality monitoring for shrimp ponds. The problems in this community service activity are: 1) the IPAL technology has not been implemented; 2) it is quite difficult for farmers to monitor water quality due to limited information regarding the interpretation of the numbers/values ​​of the tested water quality parameters. Providing solutions to these problems, a technological innovation is designed in the form of a WQ (Water Quality) Interpreter application. This community service activity aims to assist farmers in monitoring the quality of their pond water by providing information related to interpreting the numbers/values ​​of the tested water quality parameters. Community service activities are carried out through the First Session, namely the socialization of the Implementation of IPAL at the Traditional Vaname Shrimp by using a PowerPoint presentation method. The second session was training and mentoring on using the WQ Interpreter application with a demonstration method by showing the steps of using the WQ Interpreter application. The socialization for implementing IPAL at the Traditional Vaname Shrimp Shrimp and using the WQ Interpreter application was attended by about ten traditional Vaname shrimp farmers. With this socialization, knowledge about the importance of implementing IPAL for the sustainability of their shrimp farming business will increase. The WQ Interpreter application design has been completed so that the farmers can apply and use it. --- Himpunan Petambak Panarukan Situbondo (HPPS) di Kecamatan Panarukan Kabupaten Situbondo membesarkan udang vaname metode polikultur di tambak mereka secara sederhana, mengandalkan insting dengan keterbatasan pengetahuan mereka mengenai pentingnya IPAL dan monitoring kualitas air untuk tambak udang. Permasalahan dalam kegiatan pengabdian kepada masyarakat ini adalah: 1) belum diterapkannya teknologi IPAL; 2) petambak cukup kesulitan memonitoring kualitas perairan karena keterbatasan informasi mengenai interpretasi angka/nilai parameter kualitas air yang diuji. Memberikan solusi atas permasalahan tersebut, maka dirancang inovasi teknologi berupa aplikasi WQ (Water Quality) Interpreter. Tujuan kegiatan pengabdian kepada masyarakat ini adalah membantu petambak dalam memonitoring kualitas air tambaknya dengan menyediakan informasi terkait interpretasi angka/nilai parameter kualitas air yang diuji. Kegiatan pengabdian kepada masyarakat dilakukan melalui Sesi Pertama yaitu kegiatan sosialisasi Penerapan IPAL Tambak Udang Vaname Tradisional dilakukan dengan metode presentasi menggunakan power point presentation; Sesi kedua yaitu pelatihan dan pendampingan penggunaan aplikasi WQ Interpreter dengan metode demonstrasi dengan menampilkan langkah-langkah dalam penggunaan aplikasi WQ Interpreter. Kegiatan sosialisasi Penerapan IPAL Tambak Udang Vaname Tradisional dan Penggunaan aplikasi WQ Interpreter diikuti oleh sekitar 10 orang petambak udang vaname tradisional. Dengan adanya sosialisasi ini, pengetahuan mengenai pentingnya penerapan IPAL untuk keberlanjutan usaha tambak udang mereka menjadi bertambah. Perancangan aplikasi WQ Interpreter selesai dibuat hingga bisa diaplikasikan dan digunakan oleh para petambak.